Degradation of Chlorophyll Luminescence in Plants - Vakulenko, O.V.; Grygorieva, O.O.; Dacenko, O.I. (Ukrainian Journal of Physics, 2012)
The chlorophyll photoluminescence intensity degradation of Vallisneria spiralis L. water plant is studied. It is shown that the degradation curve is rather well described by a sum of two hyperbolic functions. The rate of intensity degradation reduces at low temperatures. At room temperature, a slow restoration of the luminescent system is observed after the irradiation has been ceased. No restoration is detected at the liquid nitrogen temperature. A simplified model which describes the luminescence degradation according to the quadratic law is suggested.